Studies On the Mortality of Cedrus deodara (Roxb.) L. Don. in Chail forest (H.P.) and its Causative Factors - Karthikeyan, A.; Goraya, G. S.; Kumar, Shailendra; Kalia, S. (Indian Forester, 2000)
A study has been undertaken in the diseased Cedrus deodara (Roxb.) L.Don (Deodar) forests I Chail (Himachal Pradesh) to find out the causative factor of the disease and their mortality. The infected trees showed yellowing, shortening needles and the causative pathogen was identified as Phytophora cinnamomi which is causing root rot disease. The rhizosphere soil samples of the disease-affected trees showed higher soil moisture due to blockage of water conductivity. The results of the study explicit that the fungus causes water stress in the diseased trees because of root rot. Under favourable moisture conditions the activity of the pathogen becomes vigorous. However, studies are under investigation to control the disease.